Etika Global; Sumbangan Hans Kung DALAM dialog ANTAR agama - Khairiah Husin (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2009)
This paper look at how the transition from the modern era to the post modern era of kung saw several important factors that make a paradigm in the theology of crisis. these factors are critical of the existing paradigm, every attempt to make a paradigm shift must take into account these factors include: knowledge of science, phylosophy democracy critisme of religion social science hystory and exegesis liberation movements. hat kind of paradgm most suitable for the postmodern era kung call the four dimensions that must be emanating from post modern paradigm ie dimension alkitabiyah ecumenical and politically. in the fiedof the theology he purposed a model of postmodern theology,which he called critical ecumenical theology. this model is considered appropriate theology for the needs of inter-religious dialogue